The association between internet and television access and disordered eating in a Chinese sample. Issue 6 (27th October 2014) - Peat, Christine M.; Von Holle, Ann; Watson, Hunna; Huang, Lu; Thornton, Laura M.; Zhang, Bing; Du, Shufa; Kleiman, Susan C.; Bulik, Cynthia M.
ABSTRACT Objective China has historically reported a low prevalence of eating disorders. However, the rapid social and economic development of this country as well as Western ideals widely disseminated by television and the Internet have led to distinct patterns of behavioral choices that could affect eating disorder risk. Thus, the current study explored the relation between disordered eating and media use. Method Participants were females from the 2009 wave of the China Health and Nutrition Survey (N = 1, 053). Descriptive statistics were obtained and logistic regression models, stratified by age (adolescents ages 12–17 years and adults ages 18–35 years), were used to evaluate the association of media use with disordered eating. Results In adolescents, 46.8% had access to the Internet and those with access averaged one hour per day each of Internet and television use. In adults, 41.4% had access to the Internet, and those with access averaged 1 h per day of Internet use and 2 h per day of television use. Internet access was significantly associated with a subjective belief of fatness (OR = 2.8, 95% CI: 1.6, 4.9) and worry over losing control over eating (OR = 4.8, 95% CI: 2.3, 9.8) only in adults. Discussion These findings help characterize the overall pattern of media use and report of eating disorder symptoms in a large sample of female Chinese adolescents and adults. That Internet access in adults was significantly associated with disordered eating cognitions might suggest that media access negatively influences these domains; however, more granular investigations are warranted. © 2014 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:663–669)